Gender and modern Irish drama - Harris, Susan C. (Susan Cannon), 1969- (Drama and performance studies, 2002)
Gender and Modern Irish Drama argues that the representations of sacrificial violence central to the work of the Abbey playwrights are intimately linked with constructions of gender and sexuality. Susan Cannon Harris goes beyond an examination of the relationship between Irish national drama and Irish nationalist politics to the larger question of the way national identity and gender identity are constructed through each other. Radically redefining the context in which the Abbey plays were performed, Harr.